A formação no Ensino Superior Tecnológico: estudo sobre a legislação normativa - Senff, Gerson (2017)
This research aims at investigating the formation in technological higher education in relation to its coherence and consistence, having as its source of information the primary and secondary educational legislation related to technology; primary: official documents (guidelines, decrees and reports) edited by the Ministry of Education and Culture (MEC) and other governmental entities that rule the formation of technologists and set the regulations for establishing courses; secondary: technical briefs of the Ministry of Education and Culture, (MEC) The National Institute of Educational Studies and Research Anisio Teixeira (INEP) about the registrations, new students and the ones who have completed this course modality, in order to characterize the demand for this type of teaching. The primary and secondary sources of information were obtained by the access of governmental institutions‟ portals. The theoretical presentation about formation and technology precedes the discussion of the research data. The research problem is related to the content of the official documents and the formation implemented in a technological higher education. The main hypothesis of this research departs from the assumption that the legislation and the official documents have an important role in the guidance to the courses preparation and students‟ training: the legislation for the technological higher education presents some contradictions which are inconsistent in relation to the general, vital and human formation. This research is grounded in education, formation, ideology, pseudo-formation, technological rationality, technology and technique. The results obtained from the documental analysis developed in this thesis indicate that the mentioned formation presents some problems related to the incoherence and inconsistency, with respect to the arguments used in the technological education, when the general, human and vital formation is overlooked as an indispensable element to the learners‟ development, regardless of their study level. In return, the justification in the official documents encloses recurrently and repeatedly some expressions related to technology, suggesting that education is summarized only to technology and technique